Inhibition of nNOS in the paraventricular nucleus of hypothalamus decreases exercise-induced hyperthermia - Nunan, Bruna L.C.Z.; Drummond, Lucas Rios; Rodrigues, Quezia Teixeira; Crestani, Carlos C. [UNESP]; Szawka, Raphael E.; Coimbra, Cândido Celso; da Silva, Glauber S.F. (Elsevier, 2021)
The paraventricular nucleus of the hypothalamus (PVN) is an important site for autonomic control, which integrates thermoregulation centers and sympathetic outflow to thermoeffector organs. PVN neurons express the neuronal isoform of nitric oxide synthase (nNOS) whose expression is locally upregulated by physical exercise. Thus, the aim of the present study was to evaluate the role of nNOS in the PVN in the exercise-induced hyperthermia. Seven days after surgery, male Wistar rats received bilateral intra-PVN microinjections of the selective nNOS inhibitor Nw-Propyl-L-Arginine (NPLA) or vehicle (saline) and were submitted to an acute progressive exercise session on a treadmill until fatigue. Abdominal and tail skin temperature (Tabd and Ttail, respectively) were measured, and the threshold (Hthr; °C) and sensitivity (Hsen) for heat dissipation calculated. Performance variables were also collected. During the progressive exercise protocol, all animals displayed an increase in the Tabd. However, compared to vehicle group, the microinjection of NPLA in the PVN attenuated the exercise-induced hyperthermia. There was no difference in Ttail or Hthr between NPLA and control rats. In contrast, Hsen was increased in the NPLA group compared to vehicle. In addition, heat storage was lower in NPLA-treated animals. Despite the temperature differences, inhibition of nNOS in the PVN did not affect running performance on the treadmill. These results suggest that nitrergic signaling within the PVN, under nNOS activation, drives the increase of body temperature, being necessary for the proper thermal regulatory mechanisms during progressive exercise-induced hyperthermia.
Keywords: Body temperature; Exercise thermoregulation; Hypothalamus; Nitric oxide; Physical performance; PVN